Acute effects of short-term high-intensity interval exercise and moderate-intensity aerobic exercise on food-related inhibitory control in obese adults: a randomized controlled crossover trial using ERP measures - Sun, Bo; Lu, Yun-Fei; Chen, Ji-Wei; Xiao, Yi-Lun; Ren, Jie (Frontiers in Psychology, 2025)
IntroductionFood-specific inhibitory control plays a critical role in maintaining a healthy body weight. However, limited research has explored how different exercise modalities influence this form of control in adults with obesity, particularly regarding the underlying neural mechanisms. This study aimed to examine the acute effects of short-term high-intensity interval exercise (HIIE) and moderate-intensity aerobic exercise (MIAE) on food-related inhibitory function in obese adults, and to assess whether sex differences modulate the response to exercise interventions. The findings aim to provide evidence-based guidance for the personalized design of exercise prescriptions targeting dietary behavior regulation in this population.MethodsA total of 32 obese adults participated in a within-subjects randomized crossover design. Each individual completed three separate sessions: (1) 15 min of HIIE on a power-adjusted cycle ergometer, (2) 30 min of MIAE, and (3) a 30-min resting control condition. After each session, participants performed a food-related Go/NoGo task during which behavioral responses (reaction time and accuracy) and event-related potential (ERP) components (N2 and P3 amplitudes) were recorded.ResultsAcross all image types, both male and female participants demonstrated shorter reaction times following HIIE and MIAE compared to the control condition. In males, reaction times were tended to be shorter under HIIE than under MIAE, although no significant differences in accuracy were observed across conditions. Additionally, female participants showed enhanced N2 amplitudes in NoGo trials involving low-calorie food images under the HIIE condition, and no significant difference between NoGo and Go P3 amplitudes when responding to high-calorie food stimuli.Conclusion(1) HIIE may enhance behavioral response speed in obese males through non-inhibitory optimization of the prefrontal–striatal pathway, reflecting the neural efficiency hypothesis associated with short-term exercise; (2) MIAE may improve conflict monitoring in obese females, facilitating a shift in inhibitory control over high-calorie foods from active suppression to automated processing. These findings highlight the importance of tailoring food inhibition interventions to account for exercise intensity adaptability and sex-specific neuro-metabolic targets, providing a scientific rationale for personalized exercise prescription. Future studies should further investigate the causal mechanisms through which HIIE modulates food-related inhibition and explore neuroregulatory targets for optimizing exercise-based interventions.